Preventive cardiology - Bhaskar Rao, T.; Kesava, V.; Muraleedhar, K.; Ramesh Babu, P.; Vijay Kumar, K. (India : Jaypee Brothers Medical Publishers, 2011)
Cardiovascular diseases are responsible for enormous loss of human life involving huge expenditure globally. Being responsible for almost 25 to 30% of deaths often without warning signals, stresses the fact that efforts on Preventive Cardiology with the scientific proof of its efficacy is the only viable option. This book is a useful tool to gain comprehensive knowledge of all basic aspects of common cardiovascular diseases. Hopefully this book may be a useful introduction to preventive cardiology, the medical student, postgraduates in medicine and general public to make awareness on prevention for heart disease and controlling the risk factors for heart attack (IHD), brain attack (stroke), etc.
1 Introduction 2 Conduction System Of The Heart 3 Atherosclerosis 4 Ischemic Heart Disease 5 Myocardial Infarction 6 Coronary Heart Disease 7 Stroke 8 Hyperlipidemia 9 Hypertension 10 Low Blood Pressure 11 Congenital Heart Diseases 12 Obesity And Heart Disease
Incluye contenido
Incluye índice
Keywords: CARDIOLOGY; ISCHEMIC HEART DISEASE